Pemetaan Bahasa Daerah di Provinsi Jambi - Ade Kusmana; Murfi saputra; Julisah Izar (Titian: Jurnal Ilmu Humaniora, 2018)
In general, this study aims to document the use of regional languages ​​in Jambi Province, especially in Tanjung Jabung Timur and Tanjung Jabung Barat Regency. The documentation was presented in the form of maps based on the ​​distribution area of the regional languages that was ​​researched. Then, the map contained the description of the use the regional languages ​​studied based on the social aspects of the speakers' community. Thus, it clearly illustrates the area of ​​language mapped and also as information for other researchers in conducting further research. This research in the field of sociolinguistics studies that used descriptive qualitative approach. The providing data were used observation and interviewing directly informants. Formally, the results of data analysis were presented in the form of a language region map, including information with the use of symbols or sign systems. Based on the results of the study showed, There were 5 regional languages, namely, Malay, Banjar, Bugis, Javanese, and Bajau (tungkal).